SARS-CoV-2 seroconversion among 4040 Egyptian healthcare workers in 12 resource-limited healthcare facilities: A prospective cohort study. (March 2021) - Mostafa, Aya; Kandil, Sahar; El-Sayed, Manal H; Girgis, Samia; Hafez, Hala; Yosef, Mostafa; Saber, Saly; Ezzelarab, Hoda; Ramadan, Marwa; Algohary, Eman; Fahmy, Gehan; Afifi, Iman; et al.
Abstract: Background: We examined Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) seroconversion incidence and risk factors 21 days after baseline screening among healthcare workers (HCWs) in a resource-limited setting. Methods: A prospective cohort study of 4040 HCWs took place at 12 university healthcare facilities in Cairo, Egypt; April-June 2020. Follow-up exposure and clinical data were collected through online survey. SARS-CoV-2 testing was done using rapid IgM and IgG serological tests and reverse transcriptase–polymerase chain reaction (RT-PCR) for those with positive serology. Cox proportional hazards modelling was used to estimate adjusted hazard ratios (HR) of seroconversion. Results: 3870/4040 (95.8%) HCWs tested negative for IgM, IgG and PCR at baseline; 2282 (59.0%) returned for 21-day follow-up. Seroconversion incidence (positive IgM and/or IgG) was 100/2282 (4.4%, 95% CI:3.6-5.3), majority asymptomatic (64.0%); daily hazard of 0.21% (95% CI:0.17-0.25)/48 746 person-days of follow-up. Seroconversion was: 4.0% (64/1596; 95% CI:3.1-5.1) among asymptomatic; 5.3% (36/686; 95% CI:3.7-7.2) among symptomatic HCWs. Seroconversion was independently associated with older age; lower education; contact with a confirmed case >15 min; chronic kidney disease; pregnancy; change/loss of smell; and negatively associated with workplace contact. Conclusions: Most seroconversions were asymptomatic, emphasizing need for regular universal testing. Seropositivity was three-fold that observed at baseline. Cumulative infections increased nationally by a similar rate, suggesting HCW infections reflect community not nosocomial transmission.